Vegetated Fauna Overpass Disguises Road Presence and Facilitates Permeability for Forest Microbats in Brisbane, Australia - McGregor, Mel; Matthews, Kelly; Jones, Darryl (Frontiers in Ecology and Evolution, 2017)
The effects of urbanisation on flying vertebrates historically have been underestimated, with roads in particular impacting bat populations through vehicle collisions, habitat fragmentation and unwillingness to disperse across roads. Although vegetated fauna overpasses have not traditionally been considered as beneficial for microbats, these structures have recently been identified as a potential solution for assisting microbat communities. In Brisbane, Queensland, Australia, the Compton Road fauna overpass traverses a four–lane road, facilitating connectivity for mammals, birds, reptiles and amphibians between two forest reserves. This study examined patterns of activity and species richness of microbat assemblages in relation to the Compton Road fauna overpass. Call recordings made over seven months identified nine species and two species groups (groups of species unable to be differentiated), all of which were recorded using the overpass. Bat activity on the overpass was higher than in the adjoining forest, with higher detectability. Species richness and activity at the roadside where the overpass was present was also higher than the unvegetated roadside. Activity patterns based on feeding behaviours suggest that forest species such as Nyctophilus and Myotis spp. were using the overpass, alongside more generalist species. The vegetation on the overpass is likely to be the key factor encouraging microbat activity. The Compton Road overpass appears to lessen the impact of road presence and may facilitate permeability of a major road, suggesting potential for enhancing habitat connectivity and facilitating crossings. This study is the first indication that vegetated fauna overpasses can facilitate activity and provide natural habitat continuity for diverse Australian microbat communities.